Оцінка та прогнозування пластових і порових тисків у гірському масиві шляхом математичного моделювання - Стародуб, Ю.П.; Брич, Т.Б. (Геодинаміка, 2009)
A method for estimating and predicting abnormal layer and pore pressure during drilling of oil and gas wells using finite element method is elaborated. Utilizing simulated stress-strain state of a real model of a massif it is shown the qualitative agreement of results with theoretical calculations. We identified evaluation and prediction of pore and layer pressures and reservoir in the rock massif.